A novel dynamic scheduling model for application in multimode approach - Elqabli, Zineb; Kamach, Oulaid; Khatab, Abdelhakim; Chater, Youness (Scientific reports, 2025)
This study addresses job scheduling problem in multimode systems. A multimode system is designed to perform flexibly and reliably under normal and degraded modes in highly volatile environments. A novel job dynamic scheduling optimization model is proposed to enhance the multimode system resiliency and robustness to unexpected events. The formulated optimization problem is expressed as a MILP aimed at minimizing the makespan, subject to constraints reflecting the characteristics of multimode behavior. Quantitative data were gathered through requirement documents inspired from real-life scenarios. They comprise several elements related to processing times, jobs, operations, machines employed, and RUL prediction. Various experiments are conducted to demonstrate the validity and the accuracy of the proposed approach.